AB0055 Il-1 beta and CASPASE-1 p45 expression in peripheral blood mononuclear cells of patients with adult-onset still's disease. (15th June 2017) - Bindoli, S; Fabris, F; Punzi, L; Galozzi, P; Sfriso, P
Abstract : Background: Adult-onset Still's disease (AOSD) is a systemic inflammatory condition characterized by episodes of spiking fever, evanescent rash, arthralgia, leukocytosis and hyperferritinemia. The inflammatory status of AOSD could result from a deregulation of the NLRP3 inflammasome as Interleukin-1 (IL-1) is pivotal in the pathogenesis of AOSD. Objectives: To evaluate IL-1 beta and caspase-1 p45 expression in AOSD patients. Methods: 11 AOSD patients with systemic chronic disease (mean age: 44.5±15.6 years; mean disease duration: 3.0±1.7 years) and 5 healthy donors (mean age: 41.8±7.5) were enrolled. Anakinra (in 6 patients) and DMARDs (in 5 patients) adequately controlled the disease. PBMCs (peripheral blood mononuclear cells) obtained by Ficoll centrifugation were stimulated with lipopolysaccharide (LPS) [10 ng/ml] and ATP [1 mM] for 0.5, 1, 6 and 24 hours. IL-1β level was measured in the supernatant by ELISA and the expression of caspase-1 p45 at protein level was detected by Western Blotting. Results: In unstimulated PBMCs minimal IL-1β production was found both in AOSD patients and controls. After 6 hours stimulation, IL-1β level was increased whereas we observed a reduced processing of caspase-1 p45 particularly in AOSD patients treated with Anakinra. Conclusions: Patients with refractory AOSD, who therefore need Anakinra, seem to have an increased production of IL-1β compared to healthy controls and to AOSD patients who respond to standard therapies. Altered processing of caspase-1 p45 in AOSD patients support the involvement of the NLRP3 inflammasome pathway in the pathogenesis of the disease. Disclosure of Interest: None declared